Bilayer mucoadhesive intrauterine delivery platform for sustained platelet-derived extracellular vesicle release to promote endometrial regeneration and improve implantation outcomes - Rajaganapathy Kaliyaperumal; Srinivasan R; Kalaivanan Seeni; Vignesh Sekar (Creative Pharma Assent, 2026)
Background: Endometrial dysfunction remains a major cause of implantation failure and infertility. Extracellular vesicles (EVs) derived from platelet-rich plasma have shown regenerative potential; however, their clinical application is limited by rapid clearance and poor retention within the uterine cavity. Methodology: A bilayer mucoadhesive intrauterine delivery platform was developed for sustained release of platelet-derived extracellular vesicles. The bilayer system consisted of a mucoadhesive EV-loaded layer and a protective anti-adhesion layer. Physicochemical characterization, EV release kinetics, and mucoadhesion properties were evaluated. In vitro wound healing, cell proliferation, and gene expression studies were performed. In vivo efficacy was assessed through histological evaluation of endometrial thickness and implantation outcomes. Results and Discussion: The bilayer platform demonstrated sustained extracellular vesicle release for up to 120 h with minimal initial burst release. Enhanced cell migration and proliferation, along with upregulation of endometrial receptivity markers including LIF, HOXA10, Integrin αV/β3, and IGFBP1, were observed. In vivo studies revealed significant improvement in endometrial thickness and implantation sites in the EV-Pad group compared to controls. The sustained release of EVs improved endometrial regeneration and enhanced implantation potential. The bilayer design demonstrated improved local retention characteristics and enhanced regenerative responses compared with free EV administration under experimental conditions. Conclusion: The developed bilayer mucoadhesive intrauterine delivery system provides a promising strategy for sustained EV delivery and improved endometrial regeneration, supporting its potential as a preclinical platform for sustained intrauterine regenerative delivery.